2018
DOI: 10.1007/s00231-018-2313-7
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to make a reliable assessment of the wet steam flow field in the de Laval nozzle

Abstract: This paper presents the results of research on the wet steam flow with spontaneous condensation in the de Laval nozzle. A comparison is made between the results of numerical modelling performed for two cases of boundary conditions obtained using an in-house CFD code and the Ansys CFX commercial package. The numerical modelling results are compared to the results of experimental testing carried out on an in-house laboratory steam tunnel. The differences between the numerical results produced by the two codes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…For this purpose, the X probe was used to tests carried out in a research steam tunnel located in the IMiUE Thermal Machinery Hall, used for a wide spectrum of steam flow tests, using various types of nozzles and blade channels. Research using the installation has been extensively described in publications over the last several years [14][15][16]. To carry out the tests, a measuring nozzle with the geometry shown in the figure 9, [14], and the Ansys CFX software were used.…”
Section: Determination Of the Wetness And The Diameter Of The Dropletmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the X probe was used to tests carried out in a research steam tunnel located in the IMiUE Thermal Machinery Hall, used for a wide spectrum of steam flow tests, using various types of nozzles and blade channels. Research using the installation has been extensively described in publications over the last several years [14][15][16]. To carry out the tests, a measuring nozzle with the geometry shown in the figure 9, [14], and the Ansys CFX software were used.…”
Section: Determination Of the Wetness And The Diameter Of The Dropletmentioning
confidence: 99%
“…Research using the installation has been extensively described in publications over the last several years [14][15][16]. To carry out the tests, a measuring nozzle with the geometry shown in the figure 9, [14], and the Ansys CFX software were used. Solver© s criteria and other relevant code settings have been set in accordance with Ansys recommendation for wet steam flow calculations, and detailed description of the model used, can be found in the literature [30].…”
Section: Determination Of the Wetness And The Diameter Of The Dropletmentioning
confidence: 99%
“…20,20 Dykas et al. 22 found that there are significant differences between the numerical results and experimental results in the de Laval nozzle. The International Wet Steam Modeling Project comparatively studied the numerical simulation results of numerous wet-steam methods in the nozzle, and compared them with experimental data of several nozzle test cases.…”
Section: Introductionmentioning
confidence: 98%
“…The light extinction method for estimating the liquid mass fraction in the wet steam area, is utilized in experimental studies on the steam tunnel test rig at the Silesian University of Technology's Department of Power Engineering and Turbomachinery [1]. Measuring systems based on light extinction principle were tested with the results of similar solutions from several large research centers [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%